Implementasi Algoritma Kriptografi RSA dalam Proses Enkripsi dan Dekripsi untuk Mengamankan Pesan Singkat pada Aplikasi Chatting Berbasis Web - Surbakti, Nurul; Kartika, Dinda; Lestari, Alya Dwi; Puspita, Maysi; Pandiangan , Petra Putri Sarinah; Singarimbun, Riamonda; Suryani, Windi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The rapid development of information technology, especially in online communication, raises concerns about the security and privacy of transmitted messages. Cryptography serves as a primary alternative to protect information from unauthorized access. This study aims to implement the RSA (Rivest Shamir Adleman) cryptographic algorithm to secure short messages in a web-based chat application. The research method used was a mixed method, combining literature study and application development trials. The designed application uses the Flask framework for the backend, while HTML, CSS, and JavaScript are used for the user interface. The implementation results show that the RSA algorithm successfully converted plaintext messages (e.g., "Haii") into ciphertext (such as [7347,3641,4742,4742]) using a public key and accurately restored them to the original message using a private key, without any loss of information. This application offers an interactive and visual interface, making it easier for users to understand the RSA encryption and decryption process. Testing confirmed a consistency between manual calculations and the application's functions, proving that the system works stably and accurately. It is concluded that the RSA algorithm can be used effectively to protect short messages on web-based chat platforms, serving not only as a secure communication tool but also as an effective learning medium for asymmetric cryptography concepts. For future development, it is recommended to use larger prime numbers to enhance security, as well as to add features such as file sharing and group chats.